2005
DOI: 10.1124/dmd.105.004416
|View full text |Cite
|
Sign up to set email alerts
|

Udp-Glucuronosyltransferase Isoforms Catalyzing Glucuronidation of Hydroxy-Polychlorinated Biphenyls in Rat

Abstract: ABSTRACT:Polychlorinated biphenyls (PCBs) are highly toxic environmental contaminants that can cause irreversible damage in humans and wildlife. The mechanism of toxicity is not clear, but biotransformation products such as hydroxy PCBs (OH-PCBs) are a major concern. Efforts to elucidate the metabolism of PCBs and their metabolites, however, have paid little attention to the structure of the compound to be eliminated. The objectives of this study were to clarify organ tissue distribution of the glucuronidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…It is noteworthy that UDPGA concentrations of >2mM were needed for maximal rates of glucuronidation in rat hepatic microsomes. The apparent K m and V max values reported in Table 2 were obtained with UDPGA concentrations of 3 mM (Daidoji et al, 2005) or 4 mM (Tampal et al, 2002). Hepatic concentrations of UDPGA in rats are 0.2-0.4 mM (Goon and Klaassen, 1992), thus, actual rates of glucuronidation of OH-PCBs in rat liver are likely to be lower than the V max values.…”
Section: Glucuronidationmentioning
confidence: 99%
See 3 more Smart Citations
“…It is noteworthy that UDPGA concentrations of >2mM were needed for maximal rates of glucuronidation in rat hepatic microsomes. The apparent K m and V max values reported in Table 2 were obtained with UDPGA concentrations of 3 mM (Daidoji et al, 2005) or 4 mM (Tampal et al, 2002). Hepatic concentrations of UDPGA in rats are 0.2-0.4 mM (Goon and Klaassen, 1992), thus, actual rates of glucuronidation of OH-PCBs in rat liver are likely to be lower than the V max values.…”
Section: Glucuronidationmentioning
confidence: 99%
“…The effects of food natural products on OH-PCB glucuronidation have not been studied, but OH-PCBs that are substrates for UGT1A1, or other isoforms induced by these natural products, should be more rapidly glucuronidated following exposure to flavonoids. To date, only one study has published information on the specific UGT isoforms that metabolize OH-PCBs (Daidoji et al, 2005). Expressed human UGT2B1 metabolized eight of the eleven OH-PCBs studied, UGT1A6 metabolized three of the eleven and UGT1A1 catalyzed glucuronidation of ten of the eleven OH-PCBs.…”
Section: Glucuronidationmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Daidoji et al [17] reported that the expression of UGT1A1 mRNA in normal rat liver is higher than that of UGT1A6 mRNA, while UGT1A7 mRNA is only slightly expressed. We also confirmed that the expression of UGT1A1 mRNA in liver is the highest among the three isoforms (data not shown).…”
Section: Discussionmentioning
confidence: 99%